Sono-activable and biocatalytic 3D-printed scaffolds for intelligently sequential therapies in osteosarcoma eradication and defect regeneration - Xiao Rong; Sutong Xiao; Wei Geng; Bihui Zhu; Ping Mou; Zichuan Ding; Boqing Zhang; Yujiang Fan; Li Qiu; Chong Cheng (Nature Communications)
Abstract To mitigate the necessity for multiple invasive procedures in treating malignant osteosarcoma, an innovative therapeutic approach is imperative to achieve controllable tumor-killing effects and subsequent bone repair. Here, we propose the de novo design of sono-activable and biocatalytic nanoparticles-modified 3D-printed hydroxyapatite (HA) scaffold (HS-ICTO) for intelligently sequential therapies in osteosarcoma eradication and bone defect regeneration. The engineered HS-ICTO scaffold displays superior, spatiotemporally controllable H2O2-catalytic performances, which promptly generate massive reactive oxygen species via multienzyme-like mechanisms coupled with sono-activation, thus augmenting tumor cell apoptosis. Furthermore, HS-ICTO can intelligently switch to catalyze H2O2 to O2 within the inflammatory bone defect microenvironment, effectively blocking endogenous H2O2-mediated oxidative stress, which positively modulates the osteogenic differentiation of stem cells and ultimately facilitates defect regeneration. We validate that this multifaceted HS-ICTO scaffold possesses robust and on-demand abilities to prevent neoplastic recurrence and promote anti-inflammatory osseous tissue repair, representing a promising platform for precision oncological intervention and regenerative medicine.